The Use of Information Retrieval Tools by the Postgraduate Students of Higher Educational Institutes of Pakistan - Rahoo, Liaquat Ali; Nagar, Muhammad Ali Khan; Bhutto, Arabella (Asian Journal of Contemporary Education, 2019)
The research examined the use of Information Retrieval Tools (IRTs) by the post graduate students of Mehran University of Engineering and Technology. The research used descriptive survey and was carried out over a period of six months between August 2016 and January, 2017. The sample size comprise of 2,000 postgraduate students which were randomly selected from different faculties/institutes and were served with copies of the questionnaire. A total of 1,970 copies of useable questionnaire were retrieved which represent 98.5% response rate. The responses were collated and analyzed using frequency counts and percentages. The outcome shows that respondents make use of IRTs for a variety of purposes and that university library’s user education and information literacy program forms the key source of their knowledge of IRTs’ usage. Through it, it can be safely concluded that the university library plays major role in assisting the students to make use of IRTs. Secondary findings show that the main IRTs made use of by the respondents is the Internet Search Engines. Furthermore findings of the study also revealed that the use of the tools has impacted positively on their social and academic life and has also enhanced their global knowledge of different issues. The major constraint to student’s use of the tools is that of Internet fluctuations. The paper concludes with recommendations on the need to give training on the use of IRTs to students.